Pengajuan Tuntutan (Requisitoir) Didasarkan Pada Fakta Persidangan Dalam Peradilan Militer - Arief Fahmi Lubis (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
Handing over a case to a military court is the authority of the Case Handing Officer (Papera) not the authority of the Military Prosecutor as a general summons, which is a specialty of military justice that handing over a case to a military court is an order from the Case Handing Officer (Papera) to the Military Prosecutor all summoning the public to do so. Linking the case at the conference. The purpose of this research is to analyze the existence of the authority of the Case Handing Officer (Papera) which is only directed at criminal acts committed by TNI soldiers who are under the authority of their command which is an order to the Military Prosecutor. The entire military summons the public to summon the matter at the conference. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research indicate that the submission of criminal charges (requisitoir) made by the Military Prosecutor for all general summonses must be based on a conference because the conference facts are legal facts produced through the conference examination process by analyzing all the evidence submitted.